To the problem of verification of hypotheses in hydrology - Lepikhin, A.P. (Perm Federal Research Centre Journal, 2019)
The article considers the problem of assessing the truth of scientific knowledge and outlines three approaches to determining the truth of scientific hypotheses: practicality, consistency, and coherence with the provisions of a higher order. Each approach or concept has its own evaluation criteria. These three approaches or concepts are revealed on the example of verification of three hydrological problems: the use of statistical distribution functions for estimating extreme values, the parameterization of the Chézy coefficients and the efficiency of using arithmetic averages for characterizing the chemical composition of rivers. The study shows that the transfer of technologies well-tested on interpolation tasks to solving extrapolation problems is incorrect. The variety of calculated ratios for estimating the Chézy coefficient resulted from the complexity and multiparameter nature of hydraulic resistance formation processes in channel flows, as well as the stochasticity of the morphometric parameters of natural watercourses. The article also proves the inconsistency of arithmetic average evaluations for describing the processes of hydrochemical regime of water bodies. Parametric estimates of hydrochemical indicators of water quality are characterized by significant instability of statistical characteristics. The presence of a random parameter, that is the water discharge in the denominator, makes the distribution of hydrochemical parameters closer to the Cauchy distribution for which not only the second, but also the first statistical moment do not exist.